Potential Mechanisms of Sensory Augmentation Systems on Human Balance Control - Sienko, Kathleen H.; Seidler, Rachael D.; Carender, Wendy J.; Goodworth, Adam D.; Whitney, Susan L.; Peterka, Robert J. (Frontiers in Neurology, 2018)
Numerous studies have demonstrated the real-time use of visual, vibrotactile, auditory, and multimodal sensory augmentation technologies for reducing postural sway during static tasks and improving balance during dynamic tasks. The mechanism by which sensory augmentation information is processed and used by the CNS is not well understood. The dominant hypothesis, which has not been supported by rigorous experimental evidence, posits that observed reductions in postural sway are due to sensory reweighting: feedback of body motion provides the CNS with a correlate to the inputs from its intact sensory channels (e.g., vision, proprioception), so individuals receiving sensory augmentation learn to increasingly depend on these intact systems. Other possible mechanisms for observed postural sway reductions include: cognition (processing of sensory augmentation information is solely cognitive with no selective adjustment of sensory weights by the CNS), “sixth” sense (CNS interprets sensory augmentation information as a new and distinct sensory channel), context-specific adaptation (new sensorimotor program is developed through repeated interaction with the device and accessible only when the device is used), and combined volitional and non-volitional responses. This critical review summarizes the reported sensory augmentation findings spanning postural control models, clinical rehabilitation, laboratory-based real-time usage, and neuroimaging to critically evaluate each of the aforementioned mechanistic theories. Cognition and sensory re-weighting are identified as two mechanisms supported by the existing literature.